PECULIARITIES OF ISOCYANATES INTERACTION WITH HYDRAZINE DERIVATIVES - A. D. Kirilin; L. O. Belova; N. I. Kirilina; A. V. Petrogradsky; N. L. Shembel (Тонкие химические технологии, 2018)
The results of studies on chemical transformations of organic and organosilicon isocyanates in their interaction with hydrazine derivatives have been summarized in this review. It is shown that hydrazine and its derivatives including organosilicon compounds reacting with organic isocyanates form corresponding semicarbazides readily enough. The reaction conditions that effect the composition, structure and yield of the resulting target products are presented. A significant difference in the interaction of trimethylsilyl isocyanate with organic and organosilicon derivatives of hydrazine is demonstrated. It is demonstrated that the reason for the impossibility to isolate trimethylsilyl derivatives of semicarbazide is their low hydrolytic stability, as well as high silylating ability. Peculiarities of the reaction of trimethylsilyl isocyanate and dimethylchloromethyl isocyanate silane with 1,1-dimethylhydrazine, its trimethylsilyl analog and isoniazid are given. Possible schemes for the formation of a previously unknown O-trimethylsilyl-1,1-dimethylhydrazinecarboximidoate are presented. The results of using carbofunctional organosilicon isocyanates in these processes are discussed. Basic trends in practical use of the prepared compounds as physiologically active preparations in polymer chemistry and agriculture are shown.